A stable link connectivity-based data communication through neighbour node using traffic-less path in MANET. (4th May 2020) - Ganesh, S. Sankar; Ravi, G.
Mobile Ad-hoc Network (MANET) is a collection of wireless mobile devices communicating with each other. Mobile devices are taking responsibility of routing packets between each others' nodes without any infrastructure. Generally, all the network uses the hybrid routing protocols to handle the connectivity link flow in the environment. But the hybrid rules do not consider the routing-related problems such as node selection and link analysis. So, the design of Data Communication through Neighbour Stable Link Connectivity (DC-NSLC) routing algorithm is implemented for fast and efficient traffic-less routing in the network. These routing algorithms work under the three phases, analysis of neighbour node information, neighbour node link establishment and data communication using neighbour node predicted link. Each and every phase evaluates the node movement along with the traffic design. The performance of our proposed research methodology is analysed by using the Network Simulator (NS2).